Medical English vs. Literary English: A Contrastive Analysis - AHMAD, JAMEEL (Advances in Social Sciences Research Journal, 2020)
The present study tends to determine what kinds of linguistic features and styles distinguish Medical English from literary English. Corpus analyses of both the varieties were taken into account. Ten scientific research papers drawn from each genre were linguistically analyzed. It was found that the kind of English used in Medical sciences is marked with accuracy, precision and hybridized language mixed with Latin and French. Medical scientists reveal proven facts and findings whereas literary writers just illustrate their creative thoughts with illusions, allusions and figurative language. Literary language contains non universal features and represents the artist's inner self which doesn't at all need extraneous and empirical evidence to put forth his spontaneous overflow of powerful feeling. On the contrary, medical language needs empirical experience and experimental validity. The investigation also suggests that medical English contains more passivation, nominalization, lexical density and foregrounding which are found far less in literary English. Moreover, medical scientists unlike literary artists , are adhered to a clearly defined IMRAD structure which contains Introduction, Methods, Result and Discussion sections.